A role of salt bridges in mediating drug potency: A lesson from the N-myristoyltransferase inhibitors - Spassov, Danislav S.; Atanasova, Mariyana; Doytchinova, Irini (Frontiers in Molecular Biosciences, 2023)
The salt bridge is the strongest non-covalent interaction in nature and is known to participate in protein folding, protein-protein interactions, and molecular recognition. However, the role of salt bridges in the context of drug design has remained not well understood. Here, we report that a common feature in the mechanism of inhibition of the N-myristoyltransferases (NMT), promising targets for the treatment of protozoan infections and cancer, is the formation of a salt bridge between a positively charged chemical group of the small molecule and the negatively charged C-terminus of the enzyme. Substituting the inhibitor positively charged amine group with a neutral methylene group prevents the formation of the salt bridge and leads to a dramatic activity loss. MD simulations have revealed that salt bridges stabilize the NMT- ligand complexes by functioning as molecular clips that stabilize the conformation of the protein structure. As such, the creation of salt bridges between the ligands and their protein targets may find an application as a valuable tool in rational drug design.